Who's got the power? : a practical theological reflection on the power relations in the "Blesser" phenomenon amoung female adolescence in South Africa - Jonas, Ruth (Stellenbosch : Stellenbosch University, 2019)
Thesis (MTh)--Stellenbosch University, 2019.